(untitled) (Global Journal of Human-Social Science, 2025)
This article analyzes the functionalization of possession in the Brazilian legal system highlighting its historical evolution Based on a historical-evolutionary approach and a literature review the main legal theories regarding possession are presented such as Saleilles s economic appropriation theory Perozzi s social theory and Gil s functional theory which associate possession with its economic character and social function The research emphasizes that possession by fulfilling a social and productive function becomes autonomous in relation to property which consequently loses its static nature The study highlights the main legal aspects of possessory protection such as applicable judicial actions and the possessor s rights including retention for improvements and acquisitive prescription usucapion Finally the study concludes that functionalized possession consolidates itself as a dynamic and essential instrument for achieving constitutional goals